PHENOMENON OF THE“COLOUR REVOLUTION” IN THE CONTEXT OF THE REVOLUTIONARY THEORY: THE CASE OF “TULIP REVOLUTION” IN KYRGYZSTAN - Volovoj, Vadim (Politologija, 2015)
Revolutionary studies have a long history starting from Thucydides, Plato and Aristotle, going through historians of Middle Ages and finishing by four generations of modern revolutionary research for the moment. History school (I generation) developed elaborate descriptions of the stages of some of the major social revolutions up to their day (often surprisingly accurate for later events as well) without a clear theory of “why” revolutions occurred or what accounted for their outcomes. The general theories of the 1960s (II generation) of T. R. Gurr, J. C. Davies, Ch. Johnson and others used social psychological and functionalist models to address the “why” question, but were subject to the criticism that their causal variables (relative deprivation, subsystems disequilibria, and the like) were vague, difficult to observe, or hard to measure. The third generation moved to the macrosociological level of comparing national cases in which the key variables included class relations, the state, the international economy etc. The search for causal patterns of social revolutions was pursued in Theda Skocpol’s path-breaking work “States and Social Revolution”, the 1979 capstone of third-generation structural theories. The reign of third-generation theories of revolution appears to be over. No equally dominant fourth-generation theory has yet emerged, but the lineaments of such a theory are clear. Afourth generation of revolution theory is going to reverse all of Skocpol’s key stipulations. It treats stability as problematic, sees a wide range of factors and conditions as producing departures from stability, and recognizes that the processes and outcomes of revolutions are mediated by group identity, networks, coalitions and cultural framework; leadership and competing ideologies; and the interplay among rulers, elites, popular groups, and foreign powers in response to ongoing conflicts. Still the fourth generation of revolutionary studies like all others before it can not fully explain a newly appeared phenomenon in the field of revolutionary research – “colourful revolutions” (do not to speak about many other problems of revolutionary theory, starting from the conundrum of defining revolution term and finishing by the problem of creating of the general theory of revolution). Colourful revolution (but not all researchers apply a “revolution” term to this phenomenon) is not well elaborated for the moment. It is clearly related to existing studies of revolution and may be partially explained using their insights (especially defining the causes of the revolutions), but it is unique in its implementation technique. The core idea in this context is a postmodern idea of bio-power (conception of the rule over people body and mind), firstly proposed by Michel Foucault. Practice demonstrates that the governments in post-soviet societies are hardly prepared to notice, perceive and counter applying of such technologies used by opposition, but on the other hand the examples of Belarus and Russia shows that it is possible to minimize the possibility of colourful revolutionin one separate country. In this context “ tulip revolution” in Kyrgyzstan is an example of transformation from classical violent revolution (like “Great Revolutions”) to “colourful revolution” (the most demonstrative example is “orange revolution” in the Ukraine) with a great role of accidence in this event.